Topology-guided design of an anionic bor-network for photocatalytic [Ru(bpy)3]2+ encapsulation. Issue 9 (18th December 2015) - Wang, Xuan; Lu, Weigang; Gu, Zhi-Yuan; Wei, Zhangwen; Zhou, Hong-Cai
Abstract : An anionic metal–organic framework, PCN-99, has been synthesized through a topology-guided strategy; its underlyingbor -net is realized by the use of a tetrahedral [In(COO)4 ] − node and a judiciously designed trigonal planar linker. Abstract : An anionic metal–organic framework, PCN-99, has been synthesized through a topology-guided strategy; its underlyingbor -net is realized by the use of a tetrahedral [In(COO)4 ] − node and a judiciously designed trigonal planar linker. In light of its anionic nature, the inherent cuboctahedral cage and 1D channel make PCN-99 an excellent matrix to encapsulate the photocatalytic [Ru(bpy)3 ] 2+ .